Mediating Role of Financial Transparency in Strengthening Economic Resilience - Sigit Mareta; C.M. Doktoralina; Lestari; Ranita Puspita Sari; Peter Azarya Misael Andrew Christsetyo (Jurnal Lemhannas RI, 2025)
Purpose: This study investigates the relationship between Corporate Social Responsibility (CSR) and economic resilience in coastal communities in Indonesia, with particular attention to the mediating role of financial transparency. It aims to examine how the economic, social, and environmental dimensions of CSR contribute to resilience in ecologically fragile and socio-economically vulnerable areas. Design/Methodology/Approach: This research adopts a quantitative design based on a causal model. Data were obtained through structured questionnaires administered to 100 respondents in Segarajaya Village, Bekasi Regency. Multiple linear regression was employed to analyse the direct and mediating effects of CSR and financial transparency on economic resilience. Findings: The results reveal that social CSR significantly contributes to both economic resilience and financial transparency. Environmental CSR enhances transparency but does not have a direct impact on resilience, while economic CSR demonstrates no significant effect. Financial transparency independently influences resilience yet does not mediate the relationship between CSR and resilience. Originality/Value: This study offers a novel contribution to CSR scholarship by incorporating financial transparency as a key factor in evaluating CSR effectiveness. It provides practical recommendations for developing community-oriented CSR strategies aligned with national development goals, regulatory mandates, and the broader framework of non-military national resilience. The findings emphasise the importance of financial governance in promoting inclusive and sustainable development in coastal regions.